Dyadic Interventions to Promote Physical Activity - Carr, Rachel Margaret (Curtin University, 2019)
This thesis presents a systematic review and meta-analysis of dyadic interventions (k=59) for Physical Activity (PA). Given dyadic interventions had a small positive effect on PA versus comparison conditions, including those targeting individuals; a dyadic PA program with follow-up interviews was piloted with postpartum mothers and a significant other. A small positive effect on total PA at follow-up was found for mothers in the planning group and for partners in the motivation training+ planning group.